PENERAPAN PENGAJARAN DOGMATIK DI GEREJA LOKAL UNTUK PENGUATAN IMAN JEMAAT - Jonidius Illu; Mariduk Tambun; Eliyunus Gulo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
The main problems of writing this article are, first, the emergence of dogmas in the local church that contradict or deviate from the Bible; secondly, dogmatic teaching in local churches is not a fundamental emphasis because it is considered difficult and impractical, unpleasant to discuss, and ministers in local churches do not understand and study dogmatics. The author wants to explain the application of dogmatics in the local church to strengthen the congregation's faith so that the congregation is not led astray by other dogmas or that the congregation's faith can be strengthened because of a perspective following the Bible. The research method used is qualitative research. So, it can be concluded that there needs to be dogmatics so that the local church is not influenced by dogmas that do not follow the Bible. This dogma is helpful for the firmness of the congregation's faith in the local church so that the congregation's faith becomes more substantial and can become a witness.